Epigenetic control of inflammation in Atopic Dermatitis - Sabah Akhtar (5809925) (2024)
Atopic dermatitis (AD), also known as atopic eczema, is a common but also complex chronic, itchy skin condition with underlying inflammation of the skin. This skin ailment is prevalent worldwide and affects people of all ages, particularly children below five years of age. The itching and resulting rashes in AD patients are often the result of inflammatory signals, thus necessitating a closer look at the inflammation-regulating mechanisms for putative relief, care and therapy. Several chemical- as well as genetically-induced animal models have established the importance of targeting pro-inflammatory AD microenvironment. Epigenetic mechanisms are gaining attention towards a better understanding of the onset as well as the progression of inflammation. Several physiological processes with implications in pathophysiology of AD, such as, barrier dysfunction either due to reduced filaggrin / human β‐defensins or altered microbiome, reprograming of Fc receptors with resulting overexpression of high affinity IgE receptors, elevated eosinophil numbers or the elevated IL-22 production by CD4 + T cells have underlying epigenetic mechanisms that include differential promoter methylation and/or regulation by non-coding RNAs. Reversing these epigenetic changes has been verified to reduce inflammatory burden through altered secretion of cytokines IL-6, IL-4, IL-13, IL-17, IL-22 etc, with benefit against AD progression in experimental models. A thorough understanding of epigenetic remodeling of inflammation in AD has the potential of opening avenues for novel diagnostic, prognostic and therapeutic options. Other Information Published in: Seminars in Cell & Developmental Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.semcdb.2023.04.005